Trichomonas pada IMS - Maya Olivia; Dinda Daniela Sri Putri; Sekar Keriswanie; Sonia Putri; Titin Syahwarani; Liss Dyah Dewi Arini (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Trichomoniasis is a sexually transmitted disease caused by trichomonas vaginalis that affects both women and men. In pregnant women who do not maintain personal hygiene, it can cause trichomonas vaginalis infection which results in premature rupture of membranes, premature birth, babies of mothers with trichomoniasis are more likely to have birth weights less than normal. Preterm birth While being born too early and of low birth weight are the major causes of infant deaths. The research was perfomed at the Mamajang Health Centre between March 20 and April 6, 2023. This was a laboratory observational study conducted in order to analyze the presence of Trichomonas vaginalis in the urine of pregnant women. The sample sizes taken are the sample in this study were 35 urine the samples of pregnant women at the Mamajang Health Center with purposive sampling technique. Based on the results of research conducted microscopically, it can be concluded that on positive sample was found in the urine of pregnant women with a percentage of 2.85%. Examination of urine pH, turbidity and the number of leukocytes in the sediment in the urine to see the presence of Trichomonas vaginalis urine, pregnant women.